Análise do comportamento mecânico e da durabilidade de compósitos em matriz de solo areno-argiloso reforçados com a fibra natural do coco (nucifera l) - Costa, Savila Vieira (2024)
The soils are complex materials and exhibit variability in their properties. The practice of incorporating fibers to enhance the mechanical properties of the soil dates back to ancient times. The improvement or alteration of the mechanical properties of fiber-reinforced soils depends on specific characteristics of the fibers, the type of soil, the confinement stress, and the loading mode. This study seeks to contribute to the understanding of the behavior of soil reinforced with randomly distributed coconut fibers, analyzing the effect of natural fiber degradation on the composite strength and aiming to reduce pollution caused by the disposal of these residues. For this purpose, the degradation potential of coconut fiber was analyzed through simple compression strength tests at doubled time intervals (t1= 30, t2=60, and t4=120 days) and at the control time (t0=0 days), with a fiber content of 0.5% relative to the mass of dry soil and a length of 25mm. The coconut fiber was analyzed in three different forms: the complete sample, the thicker fraction, and the finer fraction. The experimental program also included conventional triaxial tests, permeability tests, SEM, XRF, and XRD. The permeability coefficient obtained for the composite with the complete fiber sample did not show significant differences from the permeability coefficient found for natural soil. In the simple compression strength test (RCS), the natural soil (SN) showed variations in strength over the studied times, with a significant increase at time t4, a factor attributed to the sensitivity of the clayey fraction present in the soil. Through the simple compression strength test (RCS), it was observed that the hardening behavior acquired with the addition of fibers was gradually lost with increasing exposure time, up to time t2. It can be stated that exposure to climatic agents altered the rupture mechanism of the fiber-reinforced composites exposed to climatic agents. This finding is consistent with visual observations. It was noticed that the fibers became more fragile to the touch with increasing exposure time. However, at time t4, there was an increase in strength, which may be attributed to the increased strength of the composite matrix over time. The SAFF composite (soil + fine fiber sample) showed the highest strength at all analyzed times, followed by the SAFC composite (soil + complete fiber sample) and SAFG (soil + thick fiber sample). In the triaxial test, the SAFC composite and the SN showed an increase in strength from time t0 to time t4, a factor attributed to the increase in suction of the composite matrix.